Effect of Service Quality on Patient Satisfaction at Mabelopura Health Center - Pramudya, Moh Rivaldhy; Sudirman, Sudirman; Rosnawati, Rosnawati (Universitas Muhammadiyah Palu, 2021)
Quality is a measure or degree of good or bad a product or service is. Quality is a combination of the properties and characteristics of a product or service that can meet the needs of customers. The problem of research is whether there is an effect of service quality on patients' satisfaction at Mabelopura Public Health Center. This research aims to determine the effect of service quality on patients' satisfaction. This type of research is quantitative with a cross-sectional design. The sampling technique is the accidental sampling method, on 99 patients at Mabelopura Public Health Center. The analysis technique uses simple linear regression analysis. The results show that the variables which have a positive and insignificant effect on patients' satisfaction are technical competence with a coefficient of 0,087 and a sig value of 0,564> 0,05, access to services with a coefficient of 0,236 and a sig value of 0,123> 0,05, effectiveness with a coefficient value of - 0,136 and sig value 0,194> 0,05, efficiency with a coefficient value of 0,473 and a sig value of 0,049 <0,05, continuity of service with a coefficient value of 0,231 and a sig value of 0,125> 0,05, human relations with a coefficient of 0,214 and a sig value of 0,202 > 0,05, security with a coefficient value of 0,309 and a sig value of 0,055> 0,05. While the variable that has a positive and significant effect is the comfort variable with a coefficient value of 0,254 and a sig value of 0,042> 0,05. It is expected that services at the Health Center will be improved and the quality of existing services is maintained so that visitors will always feel satisfied with the service at the health center and it is hoped that service officers will serve patients fairly and according to the queue number so that there is no jealousy among patients and their satisfaction is maintained.